Liposomes Recent Advances, New Perspectives and Applications - Tyagi, Rajeev K. (IntechOpen, 2023)
The role of nanoscale drug carriers for the effective and controlled delivery of drugs and candidate antigens is instrumental in developing therapeutic and vaccine interventions for cancers, infectious diseases and beyond. As teachers of immunobiology, we think this information will contribute to the development of interventional approaches. This book, therefore, will be a valuable addition to existing knowledge in many medical schools and undergraduate courses, providing up-to-date information on drugs and their delivery for maximum therapeutic effect and vaccination potential against infectious diseases, cancers and more. Novel drugs are described, with an assessment of their effective delivery and of drug resistance, especially against cancers. The book is a timely addition to the existing literature on lipid-based nanoparticles and will be a useful resource for students, researchers, and those working in the field of drugs, drug delivery, and drug resistance in infectious and inflammatory diseases.